ДИДАКТИЧНІ УМОВИ ПОЄДНАННЯ СЛОВЕСНИХ МЕТОДІВ НАВЧАННЯ У НОВІЙ УКРАЇНСЬКІЙ ШКОЛІ - Наталя Андросова (International Journal of Innovative Technologies in Social Science, 2020)
The article describes the structure of verbal methods of teaching and didactic conditions of combining verbal methods of teaching elementary school students. The necessity of mastering the teacher effective ways of organizing teaching of elementary school students in accordance with the provisions of the State Standard and the Concept of the New Ukrainian School is substantiated. The author reveals the criteria of studying students' educational achievements, their moral education, level of motivation, sensory-empirical experience and theoretical knowledge, monologue and dialogical learning. Provides results of experimental research for 9 years in different schools of Ukraine. Notes the positive achievements of the experimental classes due to the combination of verbal teaching methods. Emphasizes the importance of improving the methodological training of the modern teacher. The author reveals the concepts of «internal dialogue», «child-centrism», «learning through activity», «interactivity of learning», «working with different sources of educational information».